2019
DOI: 10.1002/jum.15177
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Reference Ranges for Tricuspid Annular Plane Systolic Excursion and Mitral Annular Plane Systolic Excursion in Normally Grown Fetuses

Abstract: Objectives-The aim of this study was to construct reference ranges for fetal tricuspid annular plane systolic excursion (TAPSE) and mitral annular plane systolic excursion (MAPSE) using conventional M-mode ultrasound (US) in the second half of pregnancy.Abbreviations EFW, estimated fetal weight; GA, gestational age; MAPSE, mitral annular plane systolic excursion; TAPSE, tricuspid annular plane systolic excursion; US, ultrasound

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 33 publications
2
14
2
Order By: Relevance
“…Fetal reference ranges for this parameter were established [20][21][22][23]. Nevertheless, some authors have demonstrated the advantages of the STIC-M over the conventional M-mode.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fetal reference ranges for this parameter were established [20][21][22][23]. Nevertheless, some authors have demonstrated the advantages of the STIC-M over the conventional M-mode.…”
Section: Discussionmentioning
confidence: 99%
“…MAPSE reflects systolic longitudinal LV function as a useful tool in the assessment of the LV function in a variety of situations that may evolve with risks for fetal heart failure, such as maternal DM. However, limited studies on the reference values of fetal MAPSE in low-risk population have been published until now [20,23]. Recently, reference values were established for fetal MAPSE, TAPSE, and septum annular plane systolic excursion (SAPSE) using 2D and M-mode between 20 and 36.6 weeks of gestation in low-risk pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…The M-mode cursor was placed through the lateral leaflets of the AV-valves and the IVS as to obtain an alignment with the IVS <30 o . The total AVPD was measured according to previously described techniques 21,22 . An average of three measurements was calculated.…”
Section: Methodsmentioning
confidence: 99%
“…The ejection fraction is affected by ventricle shape, size, anterior load, and posterior load, which can cause some limitations in the timely diagnosis of heart failure. In the early determination of systolic dysfunction, it has been recognized recently that TAPSE and MAPSE could replace ejection fraction as an easy‐to‐apply method in neonatal intensive care units 21 . MAPSE is a simple method for the evaluation of longitudinal systolic left ventricular myocardial function and seems to be very sensitive for neonatal heart function disorders.…”
Section: Discussionmentioning
confidence: 99%